OPTIMASI KUALITAS PELAYANAN PERBANKAN DENGAN MENGGUNAKAN MODEL GOAL PROGRAMMING (STUDI KASUS PT. BANK XYZ) - Anggelinda Anggelinda; Mangara M. Tambunan; Khalida Syahputra (Jurnal Teknik Industri USU, 2014)
The level of competition in the banking world becomes more stringent that demands the bank to improve and sustain its performance. Martabe saving is the main product of Bank XYZ. However, during the last 6 months in September 2012 to March 2013, happened a decline in the number of Martabe saving’s customers about 185 customers. This research aims to do optimization service quality to meet the needs and maximize customers’s satisfaction. The methods used are Servqual, Kano Model, QFD, and Goal Programming. Based on Servqual Method, obtained that gap between received service and expected service. Then categorization attribute done by Kano Model showed that attributes of service are classified into 5 must be categories, 2 one dimensional categories and 3 attractive categories. From the creation of QFD, known that the attribute “the seriousness and speed of officers in response customers’s complaints” became the first priority in the effort to improve. Based on optimization of technical characteristics, obtained that a high level of security 79,14%, the services place and facilities are comfortable and clean 83,52%, good knowledge and skills in serving customers 100%, credibility of bank 75,32%, the development and improvement of banking technology system 100%, good responses to the needs of the customers 100%, satisfactory services 100%, the bank's strategic locations 87,78%, the number of tellers are 6 people, and the procurement of attractive banking program 80,29%.